Resolutions of IAE (First International Congress of Egyptology, 1979)
Purpose To describe the long-term clinical and imaging features of the perivascular phenotype of multifocal choroiditis with panuveitis. Methods Retrospective observational case series of eight patients (14 eyes) diagnosed with perivascular multifocal choroiditis with panuveitis at tertiary uveitis referral centers. Clinical data and multimodal imaging-including ultra-widefield color fundus photography (CFP), fundus autofluorescence (FAF), fluorescein angiography (FA), indocyanine green angiography, optical coherence tomography (OCT), and OCT angiography-were reviewed at all available visits, with analyses focused on baseline and final follow-up visits. A comprehensive systemic work-up was performed to exclude infectious, autoimmune, and neoplastic etiologies. Results Median age at presentation was 27 years (interquartile range, 17-51), with a median follow-up of 5.4 years (interquartile range, 3-10.1). Disease was bilateral in 6 of 8 patients (75%). Lesions demonstrated a reproducible perivascular distribution along retinal arteries and veins, frequently extending into the mid- and far-periphery. On CFP and FAF, lesions appeared as pigmented, hypoautofluorescent spots evolving into sharply demarcated atrophic scars. FA showed late hyperfluorescent staining without leakage. OCT revealed outer retinal and retinal pigment epithelium disruption, subretinal hyperreflective material, vertical hyperreflective column bridging the subretinal hyperreflective material and overlying retinal vessels, and progression to atrophy. Infectious and inflammatory evaluations were negative in all cases. Mild, transient anterior segment or vitreous inflammation was observed in a minority of eyes. Median BCVA remained stable at 20/25 (interquartile range, 20/32-20/20). Choroidal neovascularization occurred in 3 of 14 eyes (21%) and responded to antivascular endothelial growth factor therapy. Conclusion Perivascular multifocal choroiditis with panuveitis represents a perivascular topographic phenotype within the multifocal choroiditis with panuveitis spectrum. Recognition of perivascular multifocal choroiditis with panuveitis may improve differentiation from vasculitic and inflammatory chorioretinal mimickers.